0# Diesel water-accommodated fraction induced lipid homeostasis alteration in zebrafish embryos. (November 2018) - Mu, Xiyan; Liu, Jia; Yang, Ke; Huang, Ying; Li, Xuxing; Yang, Wenbo; Qi, Suzhen; Tu, Wenqing; Shen, Gongming; Li, Yingren
Abstract: To investigate the developmental effects and corresponding molecular mechanism of diesel in freshwater organisms, zebrafish embryos were exposed to 0# diesel water-accommodated fraction (WAF) at different concentrations. Mortality, embryonic morphological endpoints, transcriptional profile and lipid profile were evaluated after exposure. Exposure to 0# diesel WAF had no significant effect on the survival of zebrafish embryos from 1.5 to 96 hpf. However, a significant increase in mortality was observed at 144 and 196 hpf in the groups of 20 and 40 mg/L 0# diesel WAF. RNA-Seq results demonstrated that 0# diesel WAF could induce significant alterations in transcription profile at concentrations of 0.05 mg/L (the limit for petroleum hydrocarbon concentration in surface water in China) and 5 mg/L. Gene Ontology enrichment and similarity analysis indicated that lipid metabolism, lipid synthesis, biological transport, drug metabolism and homeostatic processes were the most altered biological processes after exposure to 0# diesel WAF. Further, transcription levels of genes involved in cholesterol and fatty acid synthesis were significantly inhibited by diesel WAF according to qPCR results. Lipidomics results also indicated that several lipid species (cholesterol ester, fatty acid, diglyceride and triglyceride) decreased after 0# diesel WAF exposure. These results reflect the potential risk of diesel pollution in freshwater ecosystems especially on the alteration of lipid homeostasis and enable a better understanding of the molecular pathways underlying the action of diesel WAF in zebrafish embryos. Graphical abstract: Image 1 Highlights: 0# diesel WAF altered transcription of genes are related to lipid metabolism. 0# diesel WAF could inhibit transcription of genes involved in cholesterol synthesis. 0# diesel WAF reduced levels of several lipid species of zebrafish embryos. Abstract : 0# Diesel WAF altered transcription of genes involved in lipid metabolism and reduced lipid species level in zebrafish embryos.